2009
DOI: 10.1016/j.memsci.2008.11.050
|View full text |Cite
|
Sign up to set email alerts
|

A morphological study of ceramic hollow fibre membranes

Abstract: Morphologies of ceramic hollow fibre membranes prepared from suspensions of Al 2 O 3 , NMP (Nmethyl-2-pyrrolidone) and polyethersulfone (PESf) using a dry-wet spinning/sintering process have been studied experimentally. The results indicate that two types of membrane morphologies, i.e. fingerlike and sponge-like structures can be expected. It is believed that finger-like void formation in asymmetric ceramic membranes is initiated by hydrodynamically unstable viscous fingering developed when a less viscous flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
185
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(199 citation statements)
references
References 20 publications
10
185
0
4
Order By: Relevance
“…Alumina hollow fibre membranes were prepared according to the method described by Benjamin et al [13]. The fabricating method was modified in order to obtain an asymmetric structure with finger-like supporting layers functioning as high throughput microreactors in series.…”
Section: Immobilized Proteinmentioning
confidence: 99%
See 2 more Smart Citations
“…Alumina hollow fibre membranes were prepared according to the method described by Benjamin et al [13]. The fabricating method was modified in order to obtain an asymmetric structure with finger-like supporting layers functioning as high throughput microreactors in series.…”
Section: Immobilized Proteinmentioning
confidence: 99%
“…Alumina hollow fiber membranes were prepared by a combined phase inversion and sintering technique [13]. Briefly, dispersant (Arlacel P135 1.3 wt %) was dissolved in NMP/water solutions and then aluminum oxide powders (58.7 wt %) at a ratio of 1:2:7 (0.01 µm:0.05 µm:1 µm) were added to the mixture.…”
Section: Preparation Of Alumina Hollow Fiber Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in the previous batch of HFs, the co-extrusion rate of outer layer of 0.5 cm firstly, the addition of ethanol, as a non-solvent, would increase the initial viscosity of a spinning suspension, as shown in Table 1, and secondly, the presence of ethanol would accelerate the precipitation of polymer binder during the phase inversion process because the polymer phase is closer to its precipitation point, which results in the increase of the local viscosity of the nascent fibre. The viscous fingering, [9] which is considered as the main phenomenon for the formation of the finger-like voids in the ceramic hollow fibres, has been limited by these two effects and as a result, confines the growth of finger-like voids in the fibres. As can also be seen in Figure 1, the dense electrolyte outer layer is very well-bounded to the anode inner layer, although different solvents were used for preparing the spinning suspensions of the two layers.…”
mentioning
confidence: 99%
“…Characteristics of asymmetric ceramic membranes are mainly influenced by process parameters such as suspension composition, air gap, extrusion rate, bore liquid flow rate and sintering temperature (Lee et al, 2014;Liu et al, 2003;Sun et al, 2006;Kingsbury and Li, 2009;Li et al, 2006). GarciaGarcia et al (2011GarciaGarcia et al ( 2012 showed that the increase in the sintering temperature increased the bending strength of the membrane but decreased its permeability.…”
Section: Introductionmentioning
confidence: 99%